2016
DOI: 10.1371/journal.ppat.1005414
|View full text |Cite
|
Sign up to set email alerts
|

BS69/ZMYND11 C-Terminal Domains Bind and Inhibit EBNA2

Abstract: Epstein-Barr virus (EBV) nuclear antigen 2 (EBNA2) plays an important role in driving immortalization of EBV-infected B cells through regulating the expression of many viral and cellular genes. We report a structural study of the tumor suppressor BS69/ZMYND11 C-terminal region, comprised of tandem coiled-coil-MYND domains (BS69CC-MYND), in complex with an EBNA2 peptide containing a PXLXP motif. The coiled-coil domain of BS69 self-associates to bring two separate MYND domains in close proximity, thereby enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
6
23
0
Order By: Relevance
“…Interestingly, substituting P117, the second proline of the highly conserved PXLXP motif with alanine did not negatively affect this interaction. Our observations agreed with results from a previous study, where residues in EBV EBNA2 analogous to E1A P113 and L115 were found to form hydrogen bonds with BS69, while the equivalent EBNA2 residue to E1A P117 only formed weaker van der Waals contacts [25]. Therefore, the P117A mutation may not be as detrimental since the replacement alanine residue may also form van der Waals contacts in a similar manner.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, substituting P117, the second proline of the highly conserved PXLXP motif with alanine did not negatively affect this interaction. Our observations agreed with results from a previous study, where residues in EBV EBNA2 analogous to E1A P113 and L115 were found to form hydrogen bonds with BS69, while the equivalent EBNA2 residue to E1A P117 only formed weaker van der Waals contacts [25]. Therefore, the P117A mutation may not be as detrimental since the replacement alanine residue may also form van der Waals contacts in a similar manner.…”
Section: Discussionsupporting
confidence: 91%
“…BS69 was initially discovered as a HAdV-C5 E1A interacting protein and reported to function as a strong inhibitor of E1A-dependent transactivation [22]. This 69 kDa protein is 602 residues in length, localizes to the nucleus, is ubiquitously expressed, and carries out a variety of functions associated with gene regulation [25,26,27,28]. BS69 is composed of four previously described domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, four of the top 20 TFs that co-occupy EBNA2 disorder loci with EBNA2 can be targeted by at least one available drug (MED1, p300, NFKB1, and NFKB2) 45 , and a recent study shows that the C-terminal domain of the BS69/ZMYND11 protein can bind to and inhibit EBNA2 46 . These results offer promise for the development of future therapies for manipulating the action of these proteins in individuals harboring risk alleles at EBNA2-bound loci.…”
Section: Discussionmentioning
confidence: 99%
“…BS69 (ZMYND11) is a multidomain-containing (i.e., PHD, BROMO, PWWP, and MYND) protein that was originally identified as an adenoviral early region 1A-interacting protein ( Ansieau and Leutz, 2002 ; Harter et al, 2016 ). Through its PHD–BROMO–PWWP domains, BS69 selectively recognizes histone variant H3.3 lysine 36 trimethylation (H3.3K36me3), modulates RNA Polymerase II elongation, and functions as RNA splicing regulator for intron retention ( Guo et al, 2014 ; Wen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%